Greater Celandine's Ups and Downs−21 Centuries of Medicinal Uses of Chelidonium majus From the Viewpoint of Today's Pharmacology - Zielińska, Sylwia; Jezierska-Domaradzka, Anna; Wójciak-Kosior, Magdalena; Sowa, Ireneusz; Junka, Adam; Matkowski, Adam M. (Frontiers in Pharmacology, 2018)
As antique as Dioscorides era are the first records on using Chelidonium as a remedy to several sicknesses. Inspired by the 'singatura rerum' principle and an apparent ancient folk tradition, various indications were given, such as anti-jaundice and cholagogue, pain-relieving, and quite often mentioned – ophthalmological problems. Central and Eastern European folk medicine has always been using this herb extensively. In this region, the plant is known under many unique vernacular names, especially in Slavonic languages, associated or not with old Greek relation to 'chelidon' – the swallow. Typically for Papaveroidae subfamily, yellow-colored latex is produced in abundance and leaks intensely upon injury. Major pharmacologically relevant components, most of which were first isolated over a century ago, are isoquinoline alkaloids – berberine, chelerythrine, chelidonine, coptisine, sanguinarine. Modern pharmacology took interest in this herb but it has not ended up in gaining an officially approved and evidence-based herbal medicine status. On the contrary, the number of relevant studies and publications tended to drop. Recently, some controversial reports and sometimes insufficiently proven studies appeared, suggesting anticancer properties. Anticancer potential was in line with anecdotical knowledge spread in East European countries, however, in the absence of directly-acting cytostatic compounds, some other mechanisms might be involved. Other properties that could boost the interest in this herb are antimicrobial and antiviral activities. Being a common synanthropic weed or ruderal plant, C. majus spreads in all temperate Eurasia and acclimates well to North America. Little is known about the natural variation of bioactive metabolites, including several aforementioned isoquinoline alkaloids. In this review, we put together older and recent literature data on phytochemistry, pharmacology, and clinical studies on C. majus aiming at a critical evaluation of state-of-the-art from the viewpoint of historical and folk indications. The controversies around this herb, the safety and drug quality issues and a prospective role in phytotherapy are discussed as well.